2016
DOI: 10.1111/jocn.13264
|View full text |Cite
|
Sign up to set email alerts
|

Single‐room usage patterns and allocation decision‐making in an Australian public hospital: a sequential exploratory study

Abstract: There is a trend towards increasing the proportion of single rooms in new hospital builds. Coupled with the competing clinical demands for single room care, this study highlights the complexity of nursing decision-making about patient allocation to single rooms, an issue urgently requiring further attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…14 This study also highlighted staff perceptions of the negative aspects of bed moves, which included increased patient disorientation, and workload of support staff (including cleaning, equipment relocation, etc.). 14 In the present study, within ward bed moves were also highlighted as an issue, often involving moving patients who are at high risk for falls with cognitive impairment to "more visible" areas of the ward (often close to the nurses' station).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…14 This study also highlighted staff perceptions of the negative aspects of bed moves, which included increased patient disorientation, and workload of support staff (including cleaning, equipment relocation, etc.). 14 In the present study, within ward bed moves were also highlighted as an issue, often involving moving patients who are at high risk for falls with cognitive impairment to "more visible" areas of the ward (often close to the nurses' station).…”
Section: Discussionmentioning
confidence: 78%
“…12 Patients may be moved from their initial ward location for numerous reasons, including the need to accommodate another patient, transfer to "home ward", transfer to another specialist team, patient infection, transfer to intensive care, patient behaviours, need for closer observation, changing care needs of acutely ill, clinically deteriorating patient, and patient requiring palliative care. 13,14 Increased numbers of bed moves have been reported to be associated with increased patient confusion; increased length of hospitalisation; and increased adverse clinical outcomes such as falls, medication error, or pressure ulcers. 13 Patients with greater number of bed moves have been shown to have greater levels of cognitive impairment, delirium, and frailty.…”
Section: Introductionmentioning
confidence: 99%
“…The second main map "changes of nursing" was identified in nine sources (41%; Berry, 2013;Bloomer et al, 2016;Chaudhury et al, 2006;Cusack et al, 2019;Davis et al, 2019; Figure 3. A visualization of the mapping structure for nurses' experiences.…”
Section: Conceptual Mapping and Narrative Summary Of Nurses' Experiencesmentioning
confidence: 99%
“…We see from previous studies that current isolation rooms usage is close to 100%, implying a need for temporary isolation [12]. We see the rooms as being useful for admissions deemed high risk who cannot be accommodated in an existing single room, they might also be used to control outbreaks within the hospital, or to isolate patients with highly contagious pathogens acquired in the community setting.…”
Section: Discussionmentioning
confidence: 86%
“…The extent to which all high risk patients can be effectively isolated largely depend on the number of single rooms available. While the number of beds that are in single rooms in Australian acute hospitals is not easy to know, a recent study found that total bed occupancy of single beds did not fall below 99$4%, with infection control cited as the main reason for patients being allocated to a single-bed room [12]. This suggests demand is strong for single rooms and while there is a trend for new build hospitals to have more single rooms it will likely take a long time to provide sufficient capacity.…”
Section: Introductionmentioning
confidence: 99%